2004
DOI: 10.1038/sj.ejcn.1601996
|View full text |Cite
|
Sign up to set email alerts
|

Plasma AA and DHA levels are not compromised in newly diagnosed gestational diabetic women

Abstract: Objective: The polyunsaturated fatty acids, arachidonic (AA) and docosahexaenoic (DHA), are vital structural and functional components of the neural, vascular and visual systems. There is increased demand for these fatty acids during pregnancy. Diabetes impairs the synthesis of both AA and DHA. We have investigated the possibility that pregnancy-induced diabetes compromises the levels of plasma AA and DHA in newly diagnosed expectant mothers. Design: Cross-sectional study. Setting: London, UK. Subjects and met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 31 publications
3
16
0
1
Order By: Relevance
“…Our results are in agreement with observational studies in neonates born to mothers with GDM that reported decreased percentages of DHA both in cord plasma and in cord red blood cells [28,30,31] . The reduced ratio of 13 C-DHA between cord and maternal plasma occurred not only when using the concentration ratio [26] but also with the enrichment ratio ( fig.…”
Section: Perinatal Risk Factors For Fetal Overgrowthsupporting
confidence: 83%
See 1 more Smart Citation
“…Our results are in agreement with observational studies in neonates born to mothers with GDM that reported decreased percentages of DHA both in cord plasma and in cord red blood cells [28,30,31] . The reduced ratio of 13 C-DHA between cord and maternal plasma occurred not only when using the concentration ratio [26] but also with the enrichment ratio ( fig.…”
Section: Perinatal Risk Factors For Fetal Overgrowthsupporting
confidence: 83%
“…A disturbed incorporation of DHA in maternal plasma phospholipids could affect the plasma clearance of 13 C-DHA and its placental uptake in this pathology. These results are in agreement with Thomas et al [28] , who suggested a potential failure to incorporate LC-PUFA into red cell phospholipids in addition to a defect in placental transport in GDM.…”
Section: Perinatal Risk Factors For Fetal Overgrowthsupporting
confidence: 83%
“…A better understanding of the mechanisms involved in its transfer to the neonate is important to improving fetal DHA status, not only in uncomplicated pregnancies but also in disorders associated with poor DHA status. Despite normal plasma arachidonic acid (AA) and DHA concentrations in women with gestational diabetes (5,6), low erythrocyte phospholipid long-chain polyunsaturated fatty acids (LC-PUFA) were found in their infants (7).…”
Section: Introductionmentioning
confidence: 99%
“…Fatty acid incorporation in placental lipid droplets may also interfere in their rate of fetal transfer. In fact, in GDM, a significant discrepancy between normal LC-PUFA contents in erythrocyte and plasma phospholipids of the mother but reduced LC-PUFA contents in plasma phospholipids of the neonate was found [24,25]. These data suggest that LC-PUFA transport from the placenta to the fetal circulation could be impaired in women with gestational diabetes.…”
Section: Mechanisms Involved In the Placental Transfer Of Fatty Acidsmentioning
confidence: 80%